LAB Bacteriocins Controlling the Food Isolated (Drug-Resistant) Staphylococci - Perales-Adán, Jesús; Rubiño, Susana; Martínez-Bueno, Manuel; Valdivia, Eva; Montalbán-López, Manuel; Cebrián, Rubén; Maqueda, Mercedes (Frontiers in Microbiology, 2018)
Staphylococci are a group of microorganisms that can be often found in processed food and they might pose a risk for human health. In this study we have determined the content of staphylococci in 7 different fresh goat-milk cheeses. These bacteria were present in all of them, ranging from 103-106 CFU/g based on growth on selective media. Thus, a set of 97 colonies was randomly picked for phenotypic and genotypic identification. They could be clustered by RAPD-PCR in 10 genotypes, which were assigned by 16S rDNA sequencing to four Staphylococcus species: S. aureus, S. chromogenes, S. simulans and S. xylosus. Representative strains of these species (n = 25) were tested for antibiotic sensitivity, and 11 of them were resistant to at least one of the antibiotics tested, including erythromycin, amoxicillin-clavulanic acid, oxacillin and vancomycin. We also tested two bacteriocins produced by lactic acid bacteria (LAB), namely the circular bacteriocin AS-48 and the lantibiotic nisin. These peptides have different mechanism of action at the membrane level. Nevertheless, both were able to inhibit staphylococci growth at low concentrations ranging between 0.16-0.73 µM for AS-48 and 0.02-0.23 µM for nisin, including the strains that displayed antibiotic resistance. The combined effect of these bacteriocins was tested and the fractional inhibitory concentration index was calculated. Remarkably, upon combination, they were active at the low micromolar range with a significant reduction of the minimal inhibitory concentration. Our data confirm a synergistic effect, either total or partial between AS-48 and nisin for the control of staphylococci, including antibiotic resistant strains. Collectively, these results indicate that the combined use of AS-48 and nisin could help controlling (pathogenic) staphylococci in food processing and preventing antibiotic-resistant strains reaching the consumer in the final products.